A non-invasive diagnostic test for subclinical endometritis in buffaloes - NEHRU, DAWOUD AAMIR; DHALIWAL, G S; JAN, M H; CHEEMA, R S; KUMAR, SANJAY (The Indian Journal of Animal Sciences, 2019)
This study was conducted to evaluate the potential of uterine lavage sample optical density (ULSOD) test at the time of insemination for diagnosis of subclinical endometritis (SCE). Buffaloes (86) at the time of estrus having >5% polymorphonuclear (PMN) cells in endometrial cytosmears were designated as positive (21) and buffaloes with ≤5% PMN cell as negative (65) for SCE. Presence of E. coli, A. pyogenes and F. necrophorum in the uterus was detected based upon PCR amplification of genes related to bacteria specific virulence factors (fimH, fimA and lktA genes, respectively). Pathogenic bacteria were isolated from 76.2% buffaloes with SCE as compared to 39.4% buffaloes without SCE. E. coli (fimH) and F. necrophorum (lktA) represented the major bacteriological risk factor for occurrence of SCE. The optical density of uterine lavage was measured at 352, 500, 620, 790 and 960 nm wavelengths. ULSOD620 was selected as reference wavelength because it presented the greatest area under curve (0.80). The recommended threshold for the receiver operator curve was 0.029 with a sensitivity and specificity of 85.7 and 73.8%, respectively. In the current study, the level of agreement (kappa) of ULSOD620 with cytobrush cytology was moderate (0.49) and the diagnostic accuracy was good (76.7%). Buffaloes with ≤0.029 ULSOD620 at the time of estrus had significantly lower conception rate at corresponding AI as compared to buffaloes with ≤0.029 ULSOD620. It is suggested that ULSOD620 measurement could be used as alternative to endometrial cytology and can be a tool to predict the outcome of artificial insemination in buffaloes.